Individual and combination effects of Thai herb extracts and microwave treatment against Salmonella spp. - Rachkeeree, Apinya; Phianmongkhol, Aphirak; Wirjantoro, Tri Indra (Food and Applied Bioscience Journal, 2017)
The objective of this study was to investigate the inhibition of Salmonella spp. in microbiological media or minced chicken using herb extracts and/or a microwave method. Five Thai herbs, including cinnamon (Cinnamomum cassia), garlic (Allium sativum), lemongrass (Cymbopogon citratus), clove (Eugenia caryophyllus) and ginger (Zingiber officinale), were extracted by a simultaneous distillation-extraction for 5 h and examined for their antimicrobial activities using disc diffusion and microbroth dilution assays. The antimicrobial testing revealed that the cinnamon extract exhibited the highest inhibition against all of the studied Salmonella serovars, namely Salmonella enterica serovar Typhimurium, S. enterica serovar Typhi and S. enterica serovar Enteritidis. A concentration of 30 μL cinnamon extract could produce a diameter inhibition zone of 52.89±1.16 mm against S. Typhi, while the minimum bactericidal concentration of the extract against the similar Salmonella serovar was 5 μL/mL. For the effectiveness of a microwave method to decontaminate S. Typhi and S. Enteritidis in minced chicken, two power settings of medium (450 W) and high (850 W) and processing times of 0 to 30 s were investigated. It was found that S. Typhi could be reduced by more than 0.77 log cycles after a microwave treatment at the high power setting for 30 s, while a decrease of 0.55 log cycles in the S. Typhi was determined after processing the sample at the medium power level for 30 s. When cinnamon extract at a concentration of 30 μL/25 g chicken meat was combined with a microwave heating at the high power level for 30 s, it was found that the combination treatment could decontaminate 3.56 log cycles of S. Typhi in fresh minced chicken. Finding in this study demonstrated that a combination of herb extracts and microwave process could be a useful method to control and/or inhibit the growth of Salmonella in food products, particularly chicken meat.